2017
DOI: 10.24911/ejmcr/1/2
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent fibroadenoma (Breast “Mouse”) – role of Radiology in assisting diagnosis: a case report

Abstract: Background: Fibroadenomas are quite common benign lesions in the adolescent age group but it is a cause of concern for the individual and the family. These may remain asymptomatic or may present with pain. Aesthetic distortion of the breast symmetry may lead to psychosocial morbidity in adolescent females. The diagnosis is initially made by the ultra sound. Magnetic Resonance Imaging is done in some cases where the underlying pathology is in doubt. Case presentation: We present a 21 years old young female, uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Fibroadenoma is known to present as smaller or bigger "rubbery", painless masses, freely mobile under the skin [2,4,5]. Despite that, 34.5% of our patients reported that the mass was painful.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Fibroadenoma is known to present as smaller or bigger "rubbery", painless masses, freely mobile under the skin [2,4,5]. Despite that, 34.5% of our patients reported that the mass was painful.…”
Section: Discussionmentioning
confidence: 64%
“…Fibroadenoma is quite common during reproductive period, approximately 25% of women, while incidence in adolescent girls is approximately 2% [5,18]. These tumors may occur at any age, but the peak incidence is reported in the second and third decade [18,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 A close mimicker of fibroadenoma is phyllodes tumor, subtle imaging differences like large lesions with lobulated margins, internal cystic clefts, prominent internal vascularity, and posterior acoustic enhancement should raise a suspicion of phyllodes tumor and a tissue diagnosis should be done. 4,6,7 These require wide local excision, because of the potential of local recurrence and possibility of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%